2013
DOI: 10.5606/tgkdc.dergisi.2013.5765
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early endovascular intervention on the outcome of traumatic vascular injuries

Abstract: Bu çalışmada erken dönemde anjiyografik olarak tanı konulan travmatik vasküler yaralanmaların endovasküler yöntemlerle tedavisine ilişkin orta dönem sonuçlarımız bildirildi. Ça lış ma pla nı: Ocak 2007-Aralık 2010 tarihleri arasında ateşli silah yaralanması ya da şüpheli penetran/künt travma nedeni ile kliniğimize başvuran ve vasküler yaralanma şüphesi bulunan hastalar erken dönemde incelendi. Anjiyografik değerlendirme sonrası 10 hastada vasküler yaralanma nedeni ile endovasküler tedavi uygulandı. Vasküler ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This, being minimally invasive technique, has a number of benefits including less chances of bleeding during per-operative and post-operative period, decreased duration of hospital stay and lower mortality rate. 4,18 But, in third world countries surgery remains the treatment of choice, as highlighted by Malik A et al 2 and Amirjamshidi A et al 7 too. The biggest reason behind choosing this option is non-affordability of the patients, who are subjected to huge professional fee of precious trained personals and expensive charges of endovascular inventory.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This, being minimally invasive technique, has a number of benefits including less chances of bleeding during per-operative and post-operative period, decreased duration of hospital stay and lower mortality rate. 4,18 But, in third world countries surgery remains the treatment of choice, as highlighted by Malik A et al 2 and Amirjamshidi A et al 7 too. The biggest reason behind choosing this option is non-affordability of the patients, who are subjected to huge professional fee of precious trained personals and expensive charges of endovascular inventory.…”
Section: Discussionmentioning
confidence: 95%
“…2 Though this is a late complication after primary traumatic vascular injury, false aneurysms in the victims of penetrating injury presents early as compared to those from blunt injury. 4 Post-traumatic false aneurysms do occur in increased frequency in upper and lower limb extremities, 2 but due to an increase in the number of cases from bomb blast and fire arm injuries in this region, as a result of recent war in the neighboring country and infrequent violent situations in this part of the world, we have experienced magnified number of patients who presented with pseudoaneurysms involving vessels of head and neck after suffering from roadside bomb blasts injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled bleeding and hemodynamic instability were also important factors precluding endovascular interventions; however, hybrid operating rooms with endovascular capabilities may permit more liberal use of endovascular techniques. Temizkan et al [18] suggested that early angiography in hybrid rooms during other procedures facilitated early diagnosis and treatment of vascular injuries yielding improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors contribute to the difficulty in determining the arterial damage and injury severity in the upper extremity crush injuries. [21][22][23][24] The severity of the arterial injury can be assessed more accurately with the combination of imaging data, histopathological assessment, and the direct intraoperative visualization. [19,20] Optimal treatment can be also suggested accordingly, which should be the priority of the developing treatment guidelines for the artery injuries.…”
Section: Discussionmentioning
confidence: 99%